SOME ASPECTS OF THE TEACHING OF MATHEMATICS (Conferencea, 2023)
This article discusses the problems of teaching a mathematics course. The aspects associated with reducing the amount of time devoted to mathematics in programs are highlighted. The gaps between the level of mathematical training of schoolchildren and the requirements of higher education institutions are given. Possible ways of solving some problems of the methodology of teaching mathematics at a university are proposed.